Predictors of Malnutrition among Children with Disabilities Aged 6–59 Months at Mbagathi Hospital, Kenya - KOLGAT, Eddah; MUGA, Miriam; MAIYO, Fiona (African Journal of Nutrition and Dietetics, 2025)
Childhood disability presents significant problems to health, development, and nutrition, particularly in low- and middle-income nations. There are more than 236 million disabled children all over the world, with a significant proportion in Sub-Saharan Africa. Disability prevalence in Kenya (11.4%) is similar to stunting (26%) and obesity (8%). Disabilities increase susceptibility to malnutrition because of feeding challenges, restricted mobility, frequent medical problems, and socio-economic factors. This study assessed the predictors of malnutrition in children with disabilities aged 6-59 months who presented themselves to Mbagathi County Referral Hospital, Nairobi. A hospital-based cross-sectional study comprising 160 children who had confirmed disabilities was conducted. The response was obtained by way of caregiver interviews, anthropometric data, and clinical data. The nutritional status was identified based on the WHO criterion of weight-for-age, height-for-age, weight-for-height, and mid-upper arm circumference (MUAC). The SPSS and Nutri-Survey were used to conduct data analysis, and chi-square and t-tests were used. Females were more likely to be severely malnourished and have oedema. Unemployment of caregivers (AOR=3.5), physical disability, recent illness and incomplete immunization, and feeding difficulties were predictors of underweight, while tertiary education was protective (AOR=0.41). Recent illness was found to be associated with stunting (AOR=2.5), but early breastfeeding discontinuation and deworming were protective (AOR=0.29 each). Unemployment of caregivers (AOR=3.1) and illness (AOR=2.4) were linked to wasting. This study proposed the use of specialized nutrition support, caregiver training, socioeconomic empowerment, and inclusive policies in low-resource urban areas.